Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Produk Olahan Burung Belibis (Dendrocygna arcuata) di Rumah Makan Melati Amuntai - Azwar Saihani; Aghrei Chisasmi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2014)
This aims research to (i) determine how much of the marketing mix to influence purchasing decisions of products especially processed products of grouse. (ii) Determine which of the marketing mix factors that include product, place, promotion and price that has a dominant influence the purchasing decisions of processed product of grouse. The theory used is the Marketing Management coneerning Marketing Mix Strategy and Consumer Behavior. The approach in this research is a case study that supported the survey. Type of this research is descriptive quantitative. The population in this research are 1500 consumers in one month. The sample size in this researt are 94 consumers. The data were collected by questionnaire. The hypothesis testing using multiple linear regression analysis, the F test (in unison), t test (partial) sought to determine simultaneously and partially the effect of independent variables on the dependent variable at the 95% confidence level (α = 0.05). The results show that the strategy of marketing mix consists of product, price, place, and promotion simultaneously significantly influence to purchasing the decisions of prossed products of grouse by consumers in Amuntai. Partially only one independent variable are not significantly influence to purchasing the decisions, the price variable. Most dominant variable is promotion (25.7%). The coefficient of determination (R2) indicates that the independent variable under study is able to explain 41.1% of the purchase decision variable while the remaining 58.9% is explained by other independent variables were not included in this research